Business rules systems modelling with UML and rules enforcing in active relational databases - Vasilecas, Olegas; Avdejenkov, Vladimir (Lietuvos matematikos rinkinys, 2004)
Business rules, control system of business rules, modelling of business rules by using UML diagrams and possibility to apply these systems of rules in the RDBVS are analysed in the article. Analysis showed that systems of rules could be modelled by UML and active rules of DBVS could be generated using model of rules. Possibility to describe priorities for rules, to determine conflicts between rules and recursions using UML diagrams was researched.
Keywords: business rules; business rules management systems; unified modeling language; ECA rules; bussiness rules engine